A Continental‐Scale Hydroeconomic Model for Integrating Water‐Energy‐Land Nexus Solutions. Issue 10 (11th October 2018) - Kahil, Taher; Parkinson, Simon; Satoh, Yusuke; Greve, Peter; Burek, Peter; Veldkamp, Ted I. E.; Burtscher, Robert; Byers, Edward; Djilali, Ned; Fischer, Guenther; Krey, Volker; Langan, Simon; et al.
Abstract: This study presents the development of a new bottom‐up large‐scale hydroeconomic model, Extended Continental‐scale Hydroeconomic Optimization (ECHO), that works at a subbasin scale over a continent. The strength of ECHO stems from the integration of a detailed representation of local hydrological and technological constraints with regional and global policies, while accounting for the feedbacks between water, energy, and agricultural sectors. In this study, ECHO has been applied over Africa as a case study with the aim of demonstrating the benefits of this integrated hydroeconomic modeling framework. Results of this framework are overall consistent with previous findings evaluating the cost of water supply and adaptation to global changes in Africa. Moreover, results provide critical assessments of future investment needs in both supply‐ and demand‐side water management options, economic implications of contrasting future socioeconomic and climate change scenarios, and the potential trade‐offs among economic and environmental objectives. Overall, this study demonstrates the capacity of ECHO to address challenging research questions examining the sustainability of water supply and the impacts of water management on energy and food sectors and vice versa. As such, we propose ECHO as useful tool for water‐related scenario analysis and management options evaluation. Key Points: A new large‐scale hydroeconomic model (ECHO) is developed ECHO is used to evaluate the water management adaptation pathways in Africa under various socioeconomic and climate futures Future scenario simulations highlight the capacity of ECHO to address challenging research questions related to water‐energy‐land nexus